The use of vinasse as an amendment to ex-situ bioremediation of soil and groundwater contaminated with diesel oil - Mariano, Adriano Pinto [UNESP]; Crivelaro, Sérgio Henrique Rezende [UNESP]; Angelis, Dejanira de Franceschi de [UNESP]; Bonotto, Daniel Marcos [UNESP] (Brazilian Archives of Biology and Technology, 2009)
Este trabalho investigou a possibilidade de se usar a vinhaça como um agente estimulador de processos de biorremediação ex-situ. Amostras de água subterrânea e solo foram coletadas em três postos de combustíveis. A biorremediação do solo foi simulada em frascos de Bartha, usados para medir a produção de CO2, durante 48 dias, onde a vinhaça foi adicionada a uma concentração de 33 mL.Kg-1 de solo. A eficiência de biodegradação também foi medida pela quantificação de hidrocarbonetos totais de petróleo (TPH) por cromatografia gasosa. A biorremediação da água subterrânea foi realizada em experimentos laboratoriais simulando condições aeradas (bioreatores) e não aeradas (frascos de DBO). em ambos os casos, a concentração de vinhaça foi de 5 % (v/v) e diferentes parâmetros físico-químicos foram avaliados durante 20 dias. Embora um aumento da fertilização e da população microbiana do solo foram obtidos com a vinhaça, esta estratégia não se mostrou adequada em aumentar a eficiência da biorremediação dos solos contaminados com óleo diesel. A adição de vinhaça às águas subterrâneas contaminadas teve efeitos negativos na biodegradação dos hidrocarbonetos, uma vez que a vinhaça, como uma fonte de carbono facilmente assimilável, foi preferencialmente consumida.

This work investigated the possibility of using vinasse as an amendment in ex-situ bioremediation processes. Groundwater and soil samples were collected at petrol stations. The soil bioremediation was simulated in Bartha biometer flasks, used to measure the microbial CO2 production, during 48 days, where vinasse was added at a concentration of 33 mL.Kg-1of soil. Biodegradation efficiency was also measured by quantifying the total petroleum hydrocarbons (TPH) by gas chromatography. The groundwater bioremediation was carried out in laboratory experiments simulating aerated (bioreactors) and not aerated (BOD flasks) conditions. In both the cases, the concentration of vinasse was 5 % (v/v) and different physicochemical parameters were evaluated during 20 days. Although an increase in the soil fertility and microbial population were obtained with the vinasse, it demonstrated not to be adequate to enhance the bioremediation efficiency of diesel oil contaminated soils. The addition of the vinasse in the contaminated groundwaters had negative effects on the biodegradation of the hydrocarbons, since vinasse, as a labile carbon source, was preferentially consumed.
Keywords: Bioremediation; soil; groundwater; diesel oil; biostimulation; vinasse